Russia-Ukraine Disputes based on International Law - Sanaky, Mochammad Syafruddin Rezky; Saimima, Ika Dewi Sartika; Vicky, Vicky (Pusat Kajian Keamanan Nasional (Puskamnas) Universitas Bhayangkara Jakarta Raya, 2022)
The recent escalation of tensions between Russia and Ukraine has caught the world’s attention. Tensions are characterized by the leadership of hundreds of thousands of Russian troops on Ukraine’s borders and the response of many NATO members, including the United States, to Russian pressure. NATO threats against Russia have played a role in increasing tensions on the Russia-Ukraine border. This article analyzes the nature of Russian-Ukrainian relations, the background to rising tensions between the two countries, and the international reaction to the situation. The international community must continue to seek peaceful solutions to avoid the threat of another world war. The ongoing conflict will ultimately harm many parties not only in European countries but also in other regions.